Comparison between the visco-elastic dampers and magnetorheological dampers and study the effect of temperature on the damping properties - Bhatti, A. Q. (2013)
A number of studies have been carried out to investigate the performance of visco-elastic dampers (VEDs) and Magnetorheological dampers (MRDs) in controlling the seismic response of buildings but very few studies regarding the effect of temperature on the behavior of those dampers. As the energy absorption properties of the VEDs are dependent on the ambient temperature, excitation frequency and strain amplitude. Several mathematical models have been investigated for reproducing the experimental behavior of single degree of freedom VEDs and MEDs. Of these, only the fractional derivative model can reflect the influence of temperature which is, however, so complex that it is difficult to apply in structural analysis. In order to verify the effect of temperature we took two case studies of structural element been damped once using VED and once using MRD. Kelvin-Voigt mathematical model applied and after analyzing the results, the force vs. displacement showed that MRD achieved a high force capacity and better performance than VED. Furthermore, the effect of temperature in case of VED observed via plotting the dissipated energy hysteresis at different temperature. Those results validate the effect of temperature as the lower the temperature the more viscous the dashpot element becomes and hence improved damping, but this is up to a specific low temperature.